CRITICAL DISCOURSE ANALYSIS OF CNN INDONESIA ONLINE NEWS, DECEMBER 2022 EDITION AND ITS IMPLEMENTATION IN INDONESIAN LANGUAGE LEARNING DESIGN IN JUNIOR HIGH SCHOOL - Wigati, Retno; Kamiri, Kamiri; Goziyah, Goziyah (Universitas Muhammadiyah Tangerang, 2023)
When viewed from Fairlough's analysis theory, it is found that the textual dimension which includes grammatical elements includes 7 conjunctions and 10 references, while the lexical elements include 1 synonym. Then the discursive dimension which includes elements of text production which is dominated by CNN Indonesia as the broadcaster, the dissemination of text is also dominated by CNN Indonesia's media via the You Tube link and text consumption is already very focused on events that were happening when the news was revealed in online media seen on You Tube CNN Indonesia. Com that people watch. Meanwhile, in the Practical Socio- Cultural dimension, the focus is on events that are currently happening in society both related to situational, institutional and social elements when the news is revealed in online news to the public. It is hoped that these findings will contribute to existing knowledge about critical discourse analysis research to raise awareness among researchers about articles wishing to undertake critical discourse analysis studies. In addition, the research findings can be considered by teachers and lecturers to be used as discourse learning media